The Digital Transformation of Homoeopathy in India (Advancements in Homeopathic Research, 2024)
Homoeopathy, a complementary and alternative  medicine (CAM) system, was founded by Dr Samuel  Hahnemann in 1796. Its fundamental principle is  "like cures like," which implies that any substance  capable of developing specific symptoms in a  healthy person can treat those similar symptoms in a  diseased person. India is the world's largest user and  propagator of homoeopathy.
Keywords: revolutionary; Electronic; largest